Perubahan Sudut Pandang Terorisme Paska Tragedi Penembakan di Christchurch, New Zealand : Penelitian - Yudi Hasian Harahap (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The 2019 New Zealand shootings, particularly the attacks on mosques in Christchurch, changed the way society views terrorism associated with Muslims. Despite the fact that the perpetrator was a right-wing extremist who was not a member of an Islamic group, its impact on perceptions of terrorism was significant. This article discusses the paradigm shift that occurred after the tragedy, emphasizing the fact that the media and public awareness began to recognize that terrorism is not limited to one particular religion or group. This shift highlights the importance of preventing generalizations and stereotyping of Muslims as a result of acts of terrorism carried out by individuals or small groups. In short, the New Zealand shootings have changed the way people perceive terrorism against Muslims. They also mark the beginning of a more critical and inclusive understanding of the sources of violence worldwide.